Adsorption of malathion on thermally treated egg shell material - Elwakeel, Khalid Z (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
Thermally treated egg shell materials were prepared at different temperatures. The samples were investigated by means of FT-IR and thermogravimetric analysis (TGA). The adsorption behaviour of malathion on egg shell and its thermally treated samples was studied using batch method and gave uptake capacities up to 0.964 mmol/g. Adsorption kinetics as well as the adsorption isotherms were discussed. Regeneration of the loaded adsorbent beads towards the successive cycles was also clarified. The adsorption of malathion is maintained until the third cycle without a significant activity loss